The historic importance of L. S. Vygotsky’s “the psychology of art” and some problems of modern psychological and pedagogical field - Alla Khinkanina (Universidad de San Buenaventura, 2014)
The article deals with the importance of L. S. Vygotsky’s paper “The Psychology of Art” in the present time. The shortage of ideal values is the reality of this time that in a certain way arises the issues of children and young people’s cultural evolution. Cultural and historic theory of L. S. Vygotsky touches this problem in a special way. It is the influence of art and culture, psychological and pedagogical processes that is a key element of the personality’s evolution. L. S. Vygotsky’s approach that appeared at a historic period of disturbances in the Soviet state is a fructiferous tree. This tree has a special branch that is an ethical choice between the good and evil.